(3GdJTcjd HGdUhQI aj OjhGf GMJaGdjGJ GdehejGA GdeJhMTI dYajaj eWQ (B/s - (3,eQhI eMeO Ydj GdTQja s; (3CMeO eMeO CMeO HdHhdIs; (3aGWjeG YHO GdeWdH eMehOs (2024)
(3JJfGhd gPg GdQSGdI GdUhQI YfO Yajaj eWQ, ef NdGd OjhGfg (B"(3GMJaGdjGJ GdehejGA GdeJhMTI(B"(3, eY GdJQcjR Ydi GdHfGA GdGSJYGQj; GdeONd GdefgLj GdChab dOQGSI gPG GdOjhGf, hHTcd YGe chfg TGYkQG dg QDjJg GdNGUI, hUhQg GdMjI GdeSehYI hGdeQFjI, hjJejR GdOjhGf ef Hjf OhGhjfg GdCNQi HCfg ef bUGFO GdjhejGJ, gPG HGdEVGaI Edi Cfg de jNd ef SeGJ TYQg GdCNQi GdYGeI cGdfRYI GdSQOjI, hJhXja GdMcGjI, hGdehfhdhL, hGdOjGdhL, hGSJNOGe JbfjGJ JjGQ GdhYj, hGdhGbYjI GdSMQjI, heSQMI GdbUjOI(B.s
This study examines imagery in Afifi Matar's poetry collection *"Celebrations of the Savage Mummy"*, focusing on its metaphorical structure as the most suitable methodological approach for analyzing this work. The collection reflects Matar's unique poetic vision, featuring vivid, audible, and visual images. Unlike his other collections, this one is characterized as a diary-style series of poems. Nevertheless, it retains his general poetic traits, such as a narrative inclination, the use of storytelling, monologue, dialogue, stream-of-consciousness techniques, magical realism, and the dramatization of poetry.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B196-204.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdTYQ GdYQHjs -- (3JGQjN hfbOs; (3Yajaj eWQ s -- (3GdUhQIs -- (3GMJaGdGJ GdehejGA GdeJhMTIs